Інтертекстуальний діалог: Айріс Мердок «Під сіткою» та Жан-Поль Сартр «Нудота» - Малишівська, І. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the problem of intertextuality within the novel «Under the Net». The great attention is paid to the influence that Sartre’s «Nausea» made on Iris Murdoch’s novel and to the existentialist ideas expressed in her text. In the article there are also given the examples of allusions and other means of intertextuality used in the text of the novel.